Neither Jew nor Greek?: constructing early christianity - Lieu, Judith (Studies of the New Testament and its world, 2005)
In this book, Judith Lieu explores the formation and shaping of early Christian identity within Judaism and within the wider Graeco-Roman world in the period before 200 C.E. Bringing to bear the latest analytical methods, she examines the way that literary texts presented early Christianity. She combines this with interdisciplinary historical investigation and interaction with the most recent work on Judaism in late Antiquity and on the Graeco-Roman world. The result is a very significant contribution in four of the key questions in current New Testament scholarship: how did early Christian identity come to be formed; how should we best describe and understand the processes by which the Christian movement became separate from its Jewish origins; was there anything special or different about the way women entered Judaism and early Christianity; and how did martyrdom contribute to the construction of early Christian identity?